Mesoscale-submesoscale interactions in the Gulf of Mexico: From oil dispersion to climate. (February 2019) - Bracco, Annalisa; Liu, Guangpeng; Sun, Daoxun
Abstract: In the ocean, forcing acts at planetary scales and dissipation at the microscales. In between are the mesoscales, in a lot of respects akin to nearly two-dimensional, quasi-geostrophically, balanced turbulence. Eddies and fronts, extending from ten to hundred kilometers, represent their best-known dynamical expression. At the ocean boundary layers, near the surface and at the bottom, smaller ageostrophic, coherent flow structures may appear in the form of vorticity filaments, density fronts or coherent vortices, with typical scales of hundreds of meters to few kilometers and a lifespan of few days. These so-called submesoscale circulations provide a pathway for energy transfer towards smaller scales, contribute to the global overturning budget, and impact substantially lateral and diapycnal mixing. They develop in presence of density gradients in the turbulent boundary layers, and their statistics are not well known in a global sense, but are likely to change in the future due to projected changes in near surface stratification. This perspective presents an overview of recent studies illustrating physical and biogeochemical interactions across mesoscale and submesoscale flows focusing on the Gulf of Mexico, where much modeling and observational work has been taking place following the 2010 Deepwater Horizon blow-out. The physical interpretation of several biogeochemical data-sets illustrates how mesoscale and submesoscale circulations impact the dispersion of biologically and climatically relevant tracers, from coral larvae to carbon. The ultimate goal is present the reader with examples of spatial and temporal multiscale interactions in a complex, chaotic system such as the ocean that is key to the future evolution of the climate system with its enormous storage capacity of heat and carbon.